2020
DOI: 10.1039/d0ce01070g
|View full text |Cite
|
Sign up to set email alerts
|

Smart control of calixarene polymorphic states

Abstract: An efficient strategy of polymorph screening is offered for tert-butylthiacalix[4]arene tetrasubstituted with phenacyloxy groups (1), which is based on saturation of its guest-free solid samples and inclusion compounds with guest...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…This compound was obtained from p-H-thiacalix [4]arene and 3-carboxy-1-adamantol. For comparison, we also studied p-(3-carboxy-1-adamantyl) calix [4]arene (2) and adamantylthiacalix [4]arene (3) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This compound was obtained from p-H-thiacalix [4]arene and 3-carboxy-1-adamantol. For comparison, we also studied p-(3-carboxy-1-adamantyl) calix [4]arene (2) and adamantylthiacalix [4]arene (3) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we showed that thiacalix [4]arenes with large adamantyl substituents are in the cone conformation [9,10]. It is known that carboxylic acids form dimers via H-bonds [11].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations